The Influence of Decentralization of Funding on the Effectiveness of Islamic Educational Institutions - Tiara Amalia; Febrianty Eka Putri; Siti Mutmainnah (At Turots: Jurnal Pendidikan Islam, 2025)
The decentralization of education has the potential to create gaps in the aspect of education financing, which can ultimately lead to inequality in the quality of education between regions. The implementation of regional autonomy since 2001 has brought significant changes in the governance of the education sector. Therefore, financing is a crucial element in the implementation of education. In the context of regional autonomy, the responsibility for the implementation of education from Kindergarten to Senior High School is handed over to the local government. Thus, the sustainability and quality of education are greatly influenced by the ability of the regions to manage the sector. Unfortunately, the implementation of educational autonomy by local governments has not been fully optimal, one of one of which is due to budget limitations and various other factors. Nevertheless, educational autonomy has a number of positive potentials, including improving managerial efficiency and job satisfaction of educators, producing more contextual and concrete education policies, and optimizing the use of educational resources. In addition, this autonomy allows for more optimal exploration of local potential, the preparation of an education system that is in accordance with local cultural values, and an increase in community participation. Autonomy also contributes to increased accountability, which can overall ensure the quality of education. Other positive effects that can be achieved through educational autonomy include improving the education system at the local level, efficiency in administration and finance, and providing higher quality educational services. This makes educational autonomy a strategic instrument in answering challenges in today's world of education.